Mutants and weather parameters affecting the population dynamics of three major insect pests of Mungbean - Khan, MMH; Islam, MM; Asaduzzaman, M; Uddin, MN (SAARC Journal of Agriculture, 2019)
The study was conducted to know the abundance of aphid, flea beetle and pod borer on the mutants viz., MBM-07-Y-1, MBM-07-Y-2, MBM- 656-51-2, MBM-527-114, MBM-07-(S)-2, MBM-347-13, MBM-390-94-Y, MBM-427-87-3, MBM-80 (Local) and a variety BARI moog-6 and the role of weather parameters on the population dynamics of insects at the Agricultural Farm of Patuakhali Science and Technology University from April to June, 2015. Results revealed that the tested mutants did not show resistance against aphid, flea beetle and pod borer. Mutant MBM- 347-13 had the lowest number of flea beetle while mutant MBM-427-87- 3, MBM-80(LCAL) and MBM-527-114 had the highest number of flea beetle indicating higher susceptibility to flea beetle. Mutant MBM-390-94- Y had the lowest abundance of aphid while BARI moog-6 had highest aphid abundance. Mutant MBM-347-13 had lowest number of pod borer and MBM-427-87-3 had highest abundance of pod borer followed by MBM-07(S)-2 and BARI moog-6. Flea beetle abundance gradually increased with decreasing average temperature while aphid and pod borer abundance gradually increased with increasing average temperature. In case of humidity, flea beetle abundance increased very slightly with increasing average humidity but aphid abundance increased very slightly with increasing average humidity. Pod borer abundance was low with high average humidity and then increased slightly due to decrease of humidity and finally declined with increasing humidity. SAARC J. Agri., 16(2): 1-12 (2018)